(untitled) (Economics and region, 2022)
Considering the large amount of information that is currently transmitted and consumed, for its systematization it is necessary to study certain layers of document flows in dynamics. Taking into account the latest trends in the analysis of scientific research in the world and the development of digital analytical capabilities, the use of multi-level bibliometric analysis in various fields has become a fairly popular method of processing literature. For a more detailed analysis of the study of the problem of economic crime, we conducted a bibliometric analysis, the main purpose of which is to study the bibliographic material and determine the main scientific directions in the researched field and the relationships between them. The need to study publishing activity using bibliometric analysis is primarily due to the need for effective and qualified processing of the constantly growing number of published articles on the relevant subject. The main areas of scientific literature on the specified topic can be investigated using bibliometric analysis of the concept of "economic crime" based on analytical tools Scopus, Google Trends, Web of Science. Bibliometric analysis made it possible to identify the level of research on the problem in the world and in Ukraine. The issue of economic crime in the global and domestic field of view of scientists is relevant. The paper analyzes the sources and publications on the topic of "economic crime", which are included in the Scopus scientometric database. We conducted a bibliometric analysis of scientific literature, which showed that in recent years the number of publications on the research of the chosen topic has increased significantly. An important step of bibliometric analysis is the determination of the most reliable and appropriate sources for collecting information according to the purpose of the study. Therefore, it is important to choose a database for data collection. Reference databases Web of Science Core Collections and Scopus index mainly English-language periodicals, so a large number of bibliometric studies are devoted to the analysis of English-language journal publications.